Music Modulates Autonomic Nervous System Activity in Human Fetuses - Massimello, Francesca; Billeci, Lucia; Canu, Alessio; Montt-Guevara, Maria Magdalena; Impastato, Gaia; Varanini, Maurizio; Giannini, Andrea; Simoncini, Tommaso; Mannella, Paolo (Frontiers in Medicine, 2022)
Context Fetal Autonomic Nervous sysTem Evaluation (FANTE) is a non-invasive tool which evaluates the autonomic nervous system activity in fetus. Autonomic nervous system maturation and development during prenatal life is pivotal for survival and neuropsychiatric development of the baby. Objective Aim of the study is to evaluate the effect of music stimulation on fetal heart rate, and on specific parameters linked to ANS activity, in particular on fetal heart rate variability. Methods Thirty-two women between the 32nd and 38th week with a singleton uncomplicated pregnancy were recruited. All FANTE registrations were acquired using 10-derivation electrocardiograph placed on the maternal abdomen. In each session (5 minutes basal, 10 minutes with music stimulus, and 5 minutes post-stimulus), FANTE was registered. The music stimulus was “Clair de lune” Debussy, played through headphone on the mother abdomen (CTR: 31927) Results Music does not change the mean value of fetal heart rate. However, fetal heart rate variability statistically changed during music stimulation. Heart rate variability changes depend mainly on the activation of parasympathetic branches, meanwhile no significant changes from pre-stimulus to stimulation phase were observed for sympathetic index. All the parameters remained unchanged compared to the stimulation phase after music stop. In post-stimulus phase, sympathetic index resulted in significant reduction. Conclusions Music can influence basal activity of fetal autonomic nervous system, enhancing heart rate variability, without changing fetal heart rate. Music is enabled to induce a relaxation state in near-to-term fetus, mediated by parasympathetic activation and a delayed sympathetic inhibition.